A review of rock slope stability assessment practice in Malaysia - Afiq F.A. Rahim,; Abdul G.M. Rafek,; Ailie S. Serasa,; Abd Rasid Jaapar,; Goh, Thian Lai; Rodeano Roslee,; Lee, Khai Ern; Nguyen, Xuan Huy; Tran, Van Xuan (Penerbit Universiti Kebangsaan Malaysia, 2023)
Rock slope stability assessment in Malaysia has become increasingly important as new developments encroach hillsides around major cities. This article reviews historical case studies to present a general picture of rock slope assessment practice in Malaysia, especially on methods and output of the case studies. Common methods include use of locally developed rating systems, Rock Mass Rating (RMR) and its derivatives, kinematic analysis, and numerical analysis. Application of these methods must be suitable with site conditions, while its advantages and disadvantages must be recognized by the assessor. Emergence of new technologies greatly improves the speed and quality of data acquisition provided. A total of 39 case studies on different lithologies were examined, in which progress were notable from kinematic analysis-based assessments to incorporation of rating systems and numerical analysis. This article recommends several improvements for rock slope assessment practice. These include an establishment of a local good practice guide in the assessment, incorporation of numerical analysis into standard practice, improving utilization of new technologies, more attention to the influence of weathering, and consideration of seismic influence in seismically active regions. Utilization of numerical methods and other contemporary methods reflects increasing understanding of rock mechanics which is vital to rock slope stability assessment among local practitioners. Improved rock slope assessment allows for a more accurate stability determination and decisive mitigation measure recommendations, which is to be done by competent engineering geologists, in line with Geologist Act 2008.